Предмет: Алгебра,
автор: hastay6
1
![9 - 7(x - 3) = 4x 9 - 7(x - 3) = 4x](https://tex.z-dn.net/?f=9+-+7%28x+-+3%29+%3D+4x)
2
![6x - 15 = 4x + 11 6x - 15 = 4x + 11](https://tex.z-dn.net/?f=6x+-+15+%3D+4x+%2B+11)
3
![8x - 11 = 3x + 14 8x - 11 = 3x + 14](https://tex.z-dn.net/?f=8x+-+11+%3D+3x+%2B+14)
4
![6 - 8(x + 2) = 3 - 2x 6 - 8(x + 2) = 3 - 2x](https://tex.z-dn.net/?f=6+-+8%28x+%2B+2%29+%3D+3+-+2x)
5
![17 - 12(x + 1) = 9 - 3x 17 - 12(x + 1) = 9 - 3x](https://tex.z-dn.net/?f=17+-+12%28x+%2B+1%29+%3D+9+-+3x)
Даю 35балов!!
Ответы
Автор ответа:
0
Объяснение:
1.
2.
3.
4.
5.
Похожие вопросы
Предмет: Английский язык,
автор: kyivstar290807
Предмет: Русский язык,
автор: artemmajdakov405
Предмет: Алгебра,
автор: garaevalik7997
Предмет: Химия,
автор: ramilyvay